The phenomenal forms of political graffiti in Rome and Buenos Aires: a comparison based upon detailed descriptive analysis. Issue 4 (2nd October 2018) - Penn, Roger
Abstract : The paper provides a comparison of political graffiti in Rome and Buenos Aires. It examines ten photographs in each city and explores their properties through a detailed and intensive process of descriptive coding. The comparative method reveals the specific, contextual elements essential for interpreting these graffiti. In a broader sense, these photographic images are seen not as signifying 'disorder, ' but rather as an intrinsic part of the very ordering of the streets in contemporary metropolitan environments.